An Analysis of Vegetation as a Resource in South-Eastern Nigeria - Akobundu, I. O. [et al.] (2014)
Proceedings of an International Symposium organized by the Laboratory of Soil Fertility and Soil Biology, Katholieke Universiteit Leuven (K.U. Leuven) and the International Institute of Tropical Agriculture (IITA) and held in Leuven, Belgium, 4-6 November 1991